Comparison of Shahrur's Hermeneutics and Salaf Tafsir - Muhammad Faisal Hamdani (Britain International for Academic Research (BIAR) Publisher, 2023)
This study aims are to find out comparison of shahrur's hermeneutics and salaf tafsir. The methodology of the interpretation of Shahrur and the Salaf Ulama will be seen as well as some of the results of Islamic law that were born from this methodology. The result of this study shows that Shahrur is one of the Muslim thinkers who tries to make a breakthrough for this new understanding with all his weaknesses and strengths, more or less he is able to open our doors or eyes to see other things (possibilities of other meanings) beyond the reality that exists in the traditions of the salaf manhaj which is considered by most people as something that has been established and seems undeniable or unthinkable, the corpus is closed in Arkoun's view. Shahrur has tried to declare that al-Quran, al-Kitab, al-Furqan are not the same (have different meanings), based on the context of modern science which turns out that there is no synonym in language (basically all words are different). As a result, the terms al-Zikr, Tanzil, Tartil, Thab'u al-Mathani, Muhkam, Mutashabih and others were also reconstructed by Shahrur with a different linguistic analysis than before. The offer of this thought is legitimate especially since the Prophet Muhammad himself did not define the terms clearly and consistently. From his book we can see the differences in the methodology of the interpretation of Shahrur and the Salaf both in terms of epistemology, paradigm and the side of the knowledge used to interpret. From an epistemological point of view, Shahrur prefers to use sources of interpretation, namely reason, reality and human scholarship in today's century in dialogue with the Qur’an, which is different from the salaf who stick to the interpretation of the Prophet and his companions (the early recipients of the Qur’an). As a result, Shahrur differs in defining the terms of the Qur’an with the salaf such as the terms of the Qur’an, al-Kitab, al-Furqan and others.